International humanitarian aid management within the Global Shelter Cluster 2019-2023 - selected baselines and results - Paweska Marcin; Rawłuszko Kazimierz (2024)
Abstract. The subject of this article is the selected baselines and results of the management of international humanitarian aid within the Global Shelter Cluster (GSC). The article adopts the research objective of explaining the specialisation and effects of the GSC's activities in the system of international humanitarian aid for the period 2019-2023. The research gap addressed in the article is the development of international humanitarian aid implemented through the GSC in 2019-2023.The research problem is as follows: What were the selected bases and outcomes of international humanitarian aid provided through the GSC from 2019 to 2023? A hypothesis was formulated that the functioning of the GSC was based on developed cooperation and inter-agency coordination, which allowed reaching an increasing number of people affected by humanitarian crises, with significant differences in the funding of activities across countries. For the purposes of the article, research methods were used in the form of analysis of existing data (desk research), analysis of documents published by entities managing GSC activities, and a case study for the GSC as a cluster of international humanitarian aid in the UN institutional system. The article shows that the functioning of the GSC is part of the implementation of the cluster approach in the international humanitarian system. The activities of the GSC were based on expanding the partner base and coordinating humanitarian assistance with UNHCR and IFRC. A distinction was made between Shelter Interventions (SI) and Non-Food Items Interventions (NFI). An increasing number of people affected by humanitarian crises were reached, while the funding gap for humanitarian operations in the GSC between 2019 and 2023 was reduced. Keywords: coordination, GSC, international humanitarian aid, UN, management